Middle Pleistocene large‐mammal faunas from North Iberia: palaeobiogeographical and palaeoecological implications. (27th November 2015) - Álvarez‐Lao, Diego J.
Abstract : The rich Quaternary fossil record from the Cantabrian region (NW Iberia) is virtually restricted to the Late Pleistocene, with Middle Pleistocene findings very rare. This work presents the study of two Middle Pleistocene palaeontological sites in the Cantabrian region: Llantrales quarry and Mestas de Con mine, both discovered and first described in the 1950s but never studied in detail thereafter. The material was here re‐analysed and re‐evaluated. Taxonomic attributions have been changed in most cases and, consequently, chronological assignments of the fossils have also been changed. This first detailed study of the assemblage from Llantrales quarry revealed the occurrence of the large‐sized deer Praemegaceros solilhacus, which has never been reported previously in North Iberia. Cervus cf.  elaphus and Stephanorhinus cf.  hundsheimensis were also identified. The age of these fossils was originally regarded as Pontian (late Miocene), but new palaeontological results indicate a much younger age, most likely from around 0.8 to 0.5 Ma. A taxonomic re‐evaluation of the fossils from Mestas de Con provided different results with respect to the 1950s works. The faunal association is composed of a large‐sized deer (probably corresponding to Praemegaceros ), Cervus elaphus, Capreolus cf.  capreolus, Bison sp. (small sized), Equus sp. (large sized), Stephanorhinus hemitoechus, Ursus sp. and Homotherim latidens . This faunal association was evaluated within a western European context and proves to be highly analogous to other contemporary assemblages there. The chronology was initially regarded as late Villafranchian (in a broader sense). New results, documenting the co‐occurrence of Stephanorhinus hemitoechus and Homotherium latidens, indicate a more precise and younger age, most likely between 0.6 and 0.4 Ma. These two fossil assemblages provide new and relevant information on the Middle Pleistocene faunas from a geographical region where this information, compared with other western European areas, is rare and poorly known.